Komunikasi Pemasaran Terpadu Taman Pendidikan Al-Qur’an “X”: Pendekatan Community Based Research - Wahyudiyanto, Dhanny (STID Al Hadid Surabaya, 2024)
Organizations that want to achieve success in marketing their products or services need to determine the right promotional method. Promotion does not only need to be carried out by business-oriented companies. Non-profit organizations, including Taman Pendidikan Al-Quran (TPQ), also need to determine appropriate promotional methods for the services they offer to attract the interest of their target market. TPQ